Rapid prototyping for the development of powertrain control systems - Dorey, R.E.; Maclay, D. (1996 IEEE International Symposium on Computer-Aided Control System Design, 1996)
There is enormous downward pressure on cost and the time to develop powertrain control systems. Today's automotive programs have aggressive timing, technically complex powertrains and demanding performance targets. Success depends upon producing well engineered powertrain control systems with cost and performance in careful balance. To help this one of the most important quality tools that can be applied during the development process is rapid prototyping. This provides quantitative engineering data at an early stage and an effective lever to take time and effort out of the development process. This paper explores the role of rapid prototyping in the upfront investigation phase associated with system definition, design and analysis, where a fast, but structured process is needed to progress from customer and legal requirements, associated with the vehicle platform, the market and business factors, to the point in the vehicle development program where the hardware and software are principally fixed and only relatively small modifications can be made. It is suggested that the use of rapid prototyping must be considered carefully alongside the use of CASE and CACSD tools, in order to provide the overall environment in which to engineer the architecture of the control system and develop its functionality and performance. The particular information transferred between these tools, the timing of this and the deliverables made to other parts of the vehicle development program are crucial to a successful implementation.